Comparison of neuronal activity profiles in Alzheimer's disease and frontotemporal dementia measured by resting‐state fMRI. (December 2021) - Haddad, Seyyed Mohammad Hassan; Scott, Christopher J.M.; Arnott, Stephen R.; Ozzoude, Miracle; Strother, Stephen C.; Black, Sandra E.; Borrie, Michael; Finger, Elizabeth; Trataglia, Maria Carmela; Kwan, Donna; Beaton, Derek; Symons, Sean; et al.
Abstract: Background: Neuronal activity (NA) and metabolism are impaired in the early stages of Alzheimer's Disease (AD) and Frontotemporal Dementia (FTD) leading to specific patterns of cognitive decline. Detailed disease models elucidating how and where in brain these NA disturbances commence and how they gradually progress remain incomplete. Recently, we introduced several NA metrics quantified based on fluctuations of the resting‐state fMRI (rs‐fMRI) signal. NA was significantly lower in AD and mild cognitive impairment compared to normal elderly controls (NEC). Here we extend this work using the most sensitive metric to examine NA profile differences between people with AD and FTD. Method: 3T MRI rs‐fMRI data (TR=∼2.4 Sec, 250 volumes) were obtained from the Ontario Neurodegenerative Disease Research Initiative (AD group: N=40, aged 71.8 ± 8.1, 42% female; and FTD group: N=50, aged 67.8 ± 7.3, 36% female), and Gait and Brain Study (NEC group: N=46, aged 71.0 ± 5.5, 33% female). The rs‐fMRI signal was pre‐processed and decomposed into independent components (ICs) using IC analysis. The ICs were classified into neuronal and non‐neuronal sources using a support vector machine classifier. Voxelwise NA was quantified based on the magnitude of neuronal ICs in the rs‐fMRI signal composition. This metric was utilized to create resting‐state NA maps in each subject, which were compared between groups voxel by voxel using a multiple comparisons permutation test (MCPT) with 1000 permutations . Result: Group average NA maps are provided in Fig. 1. Average NA was lower in FTD (24%) and AD (40%) compared to NEC. There was a significant difference (adjusted p ‐values from MCPT) between NEC and FTD (p<0.001), NEC and AD (p<0.001), and FTD and AD (p<0.05). Difference NA maps comparing the groups and associated significance maps are shown in Fig. 2. The FTD group had significantly higher NA compared to AD in ∼53% of brain voxels (Fig. 2). Conclusion: Significantly lower NA was detected in AD and FTD compared to NEC. Localized significant NA differences between AD and FTD were detected emerging mostly as clusters in occipital and subcortical areas that are known to be less affected by FTD.